Mutation of DNAJC19, a human homologue of yeast inner mitochondrial membrane co-chaperones, causes DCMA syndrome, a novel autosomal recessive Barth syndrome-like condition. Issue 5 (31st July 2005) - Davey, K M; Parboosingh, J S; McLeod, D R; Chan, A; Casey, R; Ferreira, P; Snyder, F F; Bridge, P J; Bernier, F P
Abstract : Background: A novel autosomal recessive condition, dilated cardiomyopathy with ataxia (DCMA) syndrome, has been identified in the Canadian Dariusleut Hutterite population, characterised by early onset dilated cardiomyopathy with conduction defects, non-progressive cerebellar ataxia, testicular dysgenesis, growth failure, and 3-methylglutaconic aciduria. Objective: To map DCMA syndrome and identify the mutation underlying this condition. Methods: A genome wide scan was undertaken on consanguineous Hutterite families using a homozygosity mapping approach in order to identify the DCMA associated chromosomal region. Mutation analysis was carried out on positional candidate genes in this region by sequencing. Reverse transcriptase polymerase chain reaction and bioinformatics analyses were then used to characterise the mutation and determine its effect on the protein product. Results: The association of DCMA syndrome with a 2.2 Mb region of chromosome 3q26.33 was found. A disease associated mutation was identified: IVS3-1 G→C in the DNAJC19 gene, encoding a DNAJ domain containing protein of previously unknown function (Entrez Gene ID 131118). Conclusions: The DNAJC19 protein was previously localised to the mitochondria in cardiac myocytes, and shares sequence and organisational similarity with proteins from several species including two yeast mitochondrial inner membrane proteins, Mdj2p and Tim14. Tim14 is a component of the yeast inner mitochondrial membrane presequence translocase, suggesting that the unique phenotype of DCMA may be the result of defective mitochondrial protein import. It is only the second human disorder caused by defects in this pathway that has been identified.